Outcomes of patients enrolled in an antiretroviral adherence club with recent viral suppression after experiencing elevated viral loads - Joseph Sharp; Lynne Wilkinson; Vivian Cox; Carol Cragg; Gilles van Cutsem; Anna Grimsrud (AOSIS, 2019)
Background: Eligibility for differentiated antiretroviral therapy (ART) delivery models has to date been limited to low-risk stable patients. Objectives: We examined the outcomes of patients who accessed their care and treatment through an ART adherence club (AC), a differentiated ART delivery model, immediately following receiving support to achieve viral suppression after experiencing elevated viral loads (VLs) at a high-burden ART clinic in Khayelitsha, South Africa. Methods: Beginning in February 2012, patients with VLs above 400 copies/mL either on first- or second-line regimens received a structured intervention developed for patients at risk of treatment failure. Patients who successfully suppressed either on the same regimen or after regimen switch were offered immediate enrolment in an AC facilitated by a lay community health worker. We conducted a retrospective cohort analysis of patients who enrolled in an AC directly after receiving suppression support. We analysed outcomes (retention in care, retention in AC care and viral rebound) using Kaplan-Meier methods with follow-up from October 2012 to June 2015. Results: A total of 165 patients were enrolled in an AC following suppression (81.8% female, median age 36.2 years). At the closure of the study, 119 patients (72.0%) were virally suppressed and 148 patients (89.0%) were retained in care. Six, 12 and 18 months after AC enrolment, retention in care was estimated at 98.0%, 95.0% and 89.0%, respectively. Viral suppression was estimated to be maintained by 90.0%, 84.0% and 75.0% of patients at 6, 12 and 18 months after AC enrolment, respectively. Conclusion: Our findings suggest that patients who struggled to achieve or maintain viral suppression in routine clinic care can have good retention and viral suppression outcomes in ACs, a differentiated ART delivery model, following suppression support.